Natural Diversity of CRISPR Spacers - Medvedeva, Sofia (CCSD, 2019)
CRISPR-Cas is a prokaryotic immunity system against mobile genetic elements, such as viruses and plasmids. The system consists of two components: the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas). In the CRISPR array, short fragments of foreign DNA, called spacers, are interleaved with palindromic repeats. During the adaptation stage of the CRISPR-Cas immunity, new spacers are inserted into the CRISPR array, whereas during the expression and interference stages, spacers are transcribed, processed and complexed with Cas proteins to target the complementary foreign DNA or RNA molecules for degradation. Analysis of CRISPR spacers is a valuable source of information about virus-host interactions, particularly powerful when applied to metagenomic data. In this work, we explored the diversity of CRISPR spacers in different natural prokaryotic communities, including extinct Escherichia coli community from a mammoth intestine, Flavobacterium communities from Antarctic surface snow, Thermus communities from four distant hot springs in Italy and Chile, and Sulfolobales community from a Japanese thermal field. The comparison of obtained environmental spacer sets with each other and with spacers from public databases as well as with sequences of viruses allowed us to reach several non-trivial conclusions and to gain insights into virus-host and virus-virus interactions in natural microbial communities. Le système CRISPR-Cas est un système immunitaire procaryote de type interférence ARN dirigé contre des éléments génétiques mobiles, tels que les virus et les plasmides. Le système consiste en un ou plusieurs loci CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats courtes répétitions palindromiques groupées et régulièrement espacées) associés à des protéines Cas (CRISPR-associated proteins) dont ils sont séparés par une séquence dite leader. Toutes les protéines Cas peuvent être fonctionnellement attribuées à des modules d'adaptation, d'expression et ...